Reinterpretation of the Qur'anic Verses on Parenting Responsibilities: A Contextual-Reflective Interpretation Study Application of Abdullah Saeed's Approach on Qs. An-Nisa' [4]:9 in the Childfree Phenomenon - Fajar Sodik; Maurisa Zinira; Lilik Rochmad Nur Choliso; Salis Irvan Fuadi; Zaenal Sukawi; Umu Salamah (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
This study aims to: 1) describe the classical interpretation of QS. An-Nisa' [4]:9, particularly the concept of protecting descendants (khaufu 'ala al-dzurriyah); 2) explain the moral message of QS. An-Nisa' [4]:9 regarding parental responsibility through Abdullah Saeed's contextual hermeneutical framework; 3) demonstrate how a reinterpretation of QS. An-Nisa' [4]:9 can provide a new, more positive, and more balanced perspective on the childfree phenomenon in contemporary society. This research adopts a qualitative method grounded in library research. The data sources include classical and contemporary tafsir works, the writings of Abdullah Saeed, thematic literature on family studies, and academic references discussing the modern emergence of the childfree phenomenon. The analysis applies a contextual hermeneutical approach that emphasizes reading the Qur'anic verse through its historical setting, universal moral values, and relevance to contemporary social realities. This approach enables an integrated understanding between the fundamental message of the verse and present-day ethical challenges. The findings reveal that classical interpretations of QS. An-Nisa' [4]:9 focuses on the protection of orphans and the obligation to prevent descendants from falling into states of weakness. The moral message of the verse, viewed through Abdullah Saeed's framework, directs attention to the heavy moral responsibility of raising children, which requires comprehensive readiness. The reinterpretation of the verse highlights that the childfree choice does not inherently conflict with Islamic values, as this decision may arise from moral responsibility to avoid producing descendants who may be at risk of weakness, as warned in the verse. This perspective encourages society to view childfree choices more positively and aligns them with the Qur'anic objective of safeguarding the well-being and strength of future generations.